Future Workforce Readiness: The Role of Upskilling and Reskilling in Enhancing Employee Performance - Naomi Ormak; Victor P. K. Lengkong; Rita N. Taroreh; Christoffel M. O. Mintardjo (Maneggio, 2026)
The accelerating pace of technological disruption, driven by artificial intelligence, automation, and digital transformation—has fundamentally altered the skills landscape of the modern workforce. This study examines the role of upskilling and reskilling programs in enhancing employee performance and building future workforce readiness. Employing a systematic literature review methodology, this paper synthesizes findings from 20 peer-reviewed articles published between 2021 and 2024 across leading international journals. The analysis identifies three primary mechanisms through which upskilling and reskilling contribute to employee performance: (1) cognitive and technical capability enhancement, (2) adaptive learning culture development, and (3) organizational resilience building. Results demonstrate that structured upskilling and reskilling initiatives, particularly those leveraging AI-enabled tools, virtual reality, and personalized learning pathways, significantly improve individual productivity, task performance, and organizational competitiveness. Furthermore, leadership support and a psychologically safe learning environment are identified as critical enablers. This study contributes a conceptual framework integrating human capital theory, dynamic capabilities, and learning organization perspectives to advance scholarly understanding of workforce readiness in the Industry 4.0–5.0 transition era.